2019
DOI: 10.1016/j.fsi.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotics in aquaculture of China—a review of the past decade

Abstract: China is the largest aquaculture producer in the world. Antibiotics were extensively used to ensure the devel-opment of the intensive aquaculture; however, the use of antibiotics causes safety-and environment-associated problems. As an alternative strategy to antibiotics, aquatic probiotics have attracted attention. The microbial organisms used as probiotics or tested as potential probiotics in Chinese aquaculture belong to various taxo-nomic divisions, including Actinobacteria, Bacteroidetes, Firmicutes, Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(135 citation statements)
references
References 193 publications
0
112
0
3
Order By: Relevance
“…The positive roles of probiotics for humans and animals, especially with the development of commercial-scale animal husbandry, have widely been accepted. Many studies have shown that the supplementation of probiotic products can improve feed efficiency and growth rate and reduce intestinal infections in many various animals (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The positive roles of probiotics for humans and animals, especially with the development of commercial-scale animal husbandry, have widely been accepted. Many studies have shown that the supplementation of probiotic products can improve feed efficiency and growth rate and reduce intestinal infections in many various animals (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies highlighted protective effects of bacteria, such as secondary endosymbionts of aphids against parasitoid wasps (Oliver et al, 2003), or symbionts of frogs against pathogenic fungi (Woodhams et al, 2007). Furthermore, microbial associates might also stimulate immunity of their hosts (Wang et al, 2019), and thus indirectly limit pathogen development.…”
Section: Introductionmentioning
confidence: 99%
“…Provision of molasses will be used by bacteria for its development. The use of bacteria can improve water quality, because it can decompose organic matter, suppress the growth of pathogens and balance the microbial community so that it can provide a better environment for fish [18] [19].…”
Section: Resultsmentioning
confidence: 99%